E-LEARNING INTEGRATION IN HIGHER EDUCATION: FOCUS ON MOROCCAN DEPARTMENTS OF ENGLISH - Laadem, Meryem (PUPIL: International Journal of Teaching, Education and Learning, 2017)
This research paper elaborates on teaching and learning English by the e-learning technology. It lays the ground for its integration in Moroccan Higher Education Institutions. Moreover, the research tries to examine the internal and external factors, which are involved in the process of integrating e-learning in the Moroccan context. The research investigates the departments of English in six higher education institutions in Morocco. First, it examines the present situation of English Language Teaching at the departments of English. Second, it tries to figure out whether positive attitudes of English educators are sufficient to advance teaching English in Moroccan universities using e-learning. The main purpose of this dissertation is to explore how teaching and learning English in higher education are performed using e-learning. The study takes the constructivism and the connectivism theories as its significant frame of investigation. These theories are joined with subjective hypothesis of learning with modern technologies. The study was based on the mixed method design to collect relevant data. It was significant to generate more information in the field work. All in all, e-learning in Morocco is still in its infancy. It requires more investigation in order to achieve the best quality of higher education.